GUT AND BUTT DESIRES AND THE HETEROSEXUAL IMAGINARY: THE PIONEER WOMAN BLOGS ABOUT FOOD, FAT, AND COWBOYS IN CHAPS - White, Michele (AoIR Selected Papers of Internet Research, 2015)
Ree Drummond, producer of The Pioneer Woman blog, associates cooking and related forms of domesticity with white heterosexual women. She dreams of a feminine world where the combination of physically touching and emotionally feeling produces clean whiteness. Through her blogged images and accounts, Drummond and many of her readers articulate a culture of shared tastes, histories, and identities and begin to trouble these positions by offering visions of the queer relationship and child—the daughter that she identifies as dirty, “man,” and husband. Drummond thus both performs a version of the “heterosexual imaginary” that, as Chrys Ingraham argues, is a “way of thinking which conceals the operation of heterosexuality in structuring gender” while constantly hinting at the queer. These queer moments are embedded in, at odds with, and support a set of deeply normalizing practices. They point to fissures in people’s claims about heterosexual identity and encourage an interrogation of the larger ways personal connections function in Internet settings.